THE USE OF ALVEOLAR CORTICOTOMY PROCEDURES IN ORTHODONTIC TREATMENT - Cristian Niky Cumpătă; Dana Cosac; Tudor Petru Ionescu (Amaltea Medical Publishing House, 2019)
Performing alveolar corticotomies shortly before the application of orthodontic forces has been suggested as a method to improve the dental movement and, consequently, the orthodontic treatment as a whole. The study evaluate whether alveolar corticotomies can accelerate tooth movements in orthodontic treatment, if they can broaden the scope of treatment for different types of dento-maxillary abnormalities, reduce the need for dental extractions and sustain long-term stability. Several techniques have been proposed, although indications, type of surgery, possible postoperative complications, treatment objectives and patient satisfaction remain unclear. The purpose of this study was to analyse whether orthodontic treatment time is reduced in patients receiving alveolar corticotomies.